IDENTIFIKASI PROSES PENGOLAHAN DAN KARAKTERISASI MUTU TUNA SIRIP KUNING (THUNNUS ALBACARES) LOIN BEKU - Yudi Prasetyo Handoko; Arpan Nasri Siregar; Ardi Yakob Rondo (Politeknik Kelautan dan Perikanan Bitung, 2021)
Yellowfin tuna has high economic value. Frozen tuna loin processing was observed and characterized its quality from raw material to finished product to deepen comprehensive understanding of the process. The aims of this research to determine the frozen tuna loin processing flow, to determine the application of the cold chain system, to calculate the yield of frozen tuna loin, and to determine the quality of raw materials and frozen tuna loin final products. The research method was conducted by observation and direct involvement during processing. This research found that processing fresh tuna into frozen tuna loin includes no less than twenty stages, from receiving raw materials to loading products for sale. The cold chain system has been implemented well because the fish temperature is always below 4 oC. The yield of frozen tuna loin processing has reached the company’s standard, which is above 50%. The organoleptic value of raw material was 8, and the final product organoleptic was also 8. The histamine test showed that tuna histamine levels were low, complied the company’s standard (< 17 ppm). The microbiology tests of raw material and final product including ALT, E. coli, and Salmonella test were less than 5×105 colonies/gram, < 3 APM/g, and negative. Keywords: Cold Chain; Frozen Loin; Quality; Tuna Processing; Yield